Pre-Clinical Studies of Epigenetic Therapies Targeting Histone Modifiers in Lung Cancer - Huffman, Kenneth; Martinez, Elisabeth D. (Frontiers in Oncology, 2013)
Treatment options for lung cancer patients have been generally limited to standard therapies or targeted interventions which involve a small number of known mutations. Although the targeted therapies are initially successful, they most often result in drug resistance, relapse and mortality. We now know that the complexity of lung cancer comes not only from genomic changes, but also from aberrant epigenetic regulatory events. Epigenetic therapies have shown promise as single agents in the treatment of hematological malignancies but have yet to meet this expectation in solid tumors thus fostering researchers to pursue new approaches in the development and use of epigenetic interventions. Here, we review some recent pre-clinical findings involving the use of drugs targeting histone modifying enzymes both as single agents and as co-therapies against lung cancer. A greater understanding of the impact of these epigenetic compounds in lung cancer signaling is needed and further evaluation in vivo is warranted in several cases based on the pre-clinical activity of a subset of compounds discussed in this review, including drugs co-targeting HDACs and EGFR, targeting Brd4 and targeting Jumonji histone demethylases.